2012
DOI: 10.1136/postgradmedj-2012-130896
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation for atrial fibrillation: who, why and does it work?

Abstract: Atrial fibrillation (AF) is the most common arrhythmia. For many years, treatment was predominantly pharmacological. The identification of signals from the pulmonary veins as critical to AF in many patients led to catheter ablation targeting these signals. Catheter ablation is more effective than antiarrhythmic drugs at restoring sinus rhythm, and may improve mortality, morbidity and quality of life in patients with symptomatic AF. There is evidence to suggest that catheter ablation would be even more benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Multiple studies have also highlighted that maintaining sinus rhythm was the most important factor in predicting stroke-free survival and lower mortality [ 15 - 17 ]. Furthermore, besides the current consensus of preserving catheter ablation for symptomatic patients with drug-refractory atrial fibrillation [ 18 ], there is sufficient evidence that catheter ablation for patients with paroxysmal AF is highly effective in curtailing progression to persistent AF [ 19 ] and achieves better results of sinus rhythm maintenance [ 20 ]. Observational studies showing a mortality benefit with catheter ablation are summarized in Table 2 .…”
Section: Reviewmentioning
confidence: 99%
“…Multiple studies have also highlighted that maintaining sinus rhythm was the most important factor in predicting stroke-free survival and lower mortality [ 15 - 17 ]. Furthermore, besides the current consensus of preserving catheter ablation for symptomatic patients with drug-refractory atrial fibrillation [ 18 ], there is sufficient evidence that catheter ablation for patients with paroxysmal AF is highly effective in curtailing progression to persistent AF [ 19 ] and achieves better results of sinus rhythm maintenance [ 20 ]. Observational studies showing a mortality benefit with catheter ablation are summarized in Table 2 .…”
Section: Reviewmentioning
confidence: 99%
“…1,2 RF ablation of AF is more effective than anti-arrhythmic drugs at restoring sinus rhythm and may improve mortality, morbidity and quality of life in patients with symptomatic AF. 3,4 AF is the most common cardiac arrhythmia. 4 Several studies have shown that visualisation could be a suitable adjunct to the usual analgesics used during medical invasive procedures, and effectively reduce the patient's perception of pain intensity and anxiety during the procedures.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 RF ablation of AF is more effective than anti-arrhythmic drugs at restoring sinus rhythm and may improve mortality, morbidity and quality of life in patients with symptomatic AF. 3,4 AF is the most common cardiac arrhythmia. 4…”
Section: Introductionmentioning
confidence: 99%